Balancing acts : women principals at work - Smulyan, Lisa (SUNY series in women in education., 2000)
"Balancing Acts uses life history and ethnography to examine the lives and work of three female elementary school principals and highlights their daily use of personal and professional skills. Smulyan examines the principals' personal backgrounds and their effect on their work within the community they serve, their school, and the historical and social structures that frame their actions and interactions. What emerges is a fascinating personal view of the dilemmas, decisions, and consequences faced by the female principalship."--Jacket